A GaAs Low Noise Amplifier for 2.4 GHz ISM band Applications - Ribate, Mohamed; Mandry, Rachid; Elabdellaoui, Larbi; Benbrahim, Mohammed (ITM web of conferences, 2022)
In this paper, a Low Noise Amplifier (LNA) operating in the Industrial Scientific and Medical (ISM) band of 2.45 GHz is proposed. The designed LNA is based on GaAs ATF21170 active device. To improve gain and matching parameters, a hybrid matching technique based on smith chart and optimization is used. The proposed biasing network as well as the stabilization circuit allow achieving a minimum noise figure with an unconditionally stability over the whole operating frequency ranging from 2.25 GHz to 2.55 GHz. Finally, some tradeoffs were done to obtain the minimum noise figure with the greatest available power gain. In terms of performances, the proposed structure shows an excellent noise figure of ~1Db.The simulated results show an excellent input/output return loss under -15 dB over the operation frequency band with an excellent small signal gain ranging between 17 dB and 15 dB. In terms of large signal performance, the proposed LNA achieves an output power of 17 dBm (52 mW) with a PAE of 22% and an output intercept IP3 around 27 dBm.